PEMBERIAN TERAPI BERMAIN DENGAN TEKNIK BERCERITA TERHADAP KOOPERATIF ANAK USIA PRA SEKOLAH - Yendrizal Jafri (LPPM UNIVERSITAS PERINTIS INDONESIA, 2017)
The situation underwent a long hospitalization can make children depressed and stressed. In these circumstances children tend not to cooperate so that quick-tempered, cranky and generally become difficult to face. In early studies in hospitals Solok found of 9 children, 3 children crying, 5 children closer to parents, and 3 of them did not want to answer the questions the nurse when performing the action. The purpose of this research is to know is there any relationship between the provision of play therapy with telling techniques of the level of cooperative pre-school age children in Pediatric of Regional Public Hospital Solok. This research is a quantitative approach to quasi experimental design involving pre-school aged children as many as 15 children are given play therapy with the technique of telling stories and 15 children not given play therapy with the technique of storytelling. Measuring instrument in the form of guidelines for observation and analysis used were paired t test. Of the 15 children not given play therapy with telling techniques most uncooperative even as many as 80% and the cooperative is only a fraction as many as 20%. Meanwhile of the 15 children who were given therapy plays only a small part of a cooperative is not as much as 33.3% and a cooperative of more than half as many as 66.7%. From the statistical test results obtained value p value = 0.014 where p-value <α (0.05), then Ho is rejected with the conclusion there is a connection with the provision of play therapy techniques to tell the level of cooperative children who were hospitalized. It can be concluded that the granting of play therapy with the technique say more influential than play therapy is not given in creating cooperation among children being treated. The researcher recommends for further research in the field of nursing in order to continue research on the factors associated with the cooperative attitude of children in care in child care spaces.